Cross-country fiscal policy spillovers and capital-skill complementarity in currency unions - Thomas Davione; Matthias Molnar (Institute for Advanced Studies (IHS), 2017)
We investigate cross-country fiscal policy spillovers through the integration of capital markets in a currency union and allow capital use in production to differ across countries. Following empirical evidence, we assume that production exhibits capital-skill complementarity. Using a multi-country overlapping-generations model calibrated for 14 European Union countries, we find that output spillovers are small with standard tax reforms but can be sizeable with large government spending increases financed by taxes: long run output losses in shock-free countries can amount to a quarter of the losses in countries hit by the spending shock. Conditional and temporary relaxing of the EU debt ceiling rule could benefit the Union as a whole.
Keywords: C68; E62; F21; F45; 330; spillovers; fiscal policy; capital-skill complementarity; multi-country modeling; computable general equilibrium